1979
DOI: 10.1080/15287397909529795
|View full text |Cite
|
Sign up to set email alerts
|

Environmental lead and children: The Omaha study

Abstract: Blood lead (Pb B) was determined in 1232 samples from 831 children in Omaha and correlated with air lead (Pb A) concentrations of 0.02-1.69 microgram/m3 from 1971 to 1977. A bivariate equation for ages 6-18 yr based on these data predicts an increase in Pb B of 1.4 microgram/dl as Pb A increases from 1 to 2 microgram/m3. Pb B increases 7 microgram/dl as the mean values for soil and house dust Pb increase from 100 to 750 microgram/g. Multiple regression analysis shows that the combined effects of air, soil, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…A recent study by Elwood et al (53) among preschool children in Wales showed no difference in the mean blood-lead level of a group living adjacent to busy major roads compared with that of a group living in a rural area. By contrast, some work from the United States (54)(55)(56) suggests that the blood-lead levels of urban children may be about 10 ,ug/dL higher than those of rural children (such a large difference could not be accounted for by the inhalation route alone) although it must be noted that there were difficulties in matching for race. Again, in a study of urban and suburban school children (aged 10-15 years) in Tokyo, Okubo et al (57) found significantly higher blood-lead levels in the urban groups.…”
Section: Discussionmentioning
confidence: 85%
“…A recent study by Elwood et al (53) among preschool children in Wales showed no difference in the mean blood-lead level of a group living adjacent to busy major roads compared with that of a group living in a rural area. By contrast, some work from the United States (54)(55)(56) suggests that the blood-lead levels of urban children may be about 10 ,ug/dL higher than those of rural children (such a large difference could not be accounted for by the inhalation route alone) although it must be noted that there were difficulties in matching for race. Again, in a study of urban and suburban school children (aged 10-15 years) in Tokyo, Okubo et al (57) found significantly higher blood-lead levels in the urban groups.…”
Section: Discussionmentioning
confidence: 85%
“…These areas are characterized by elevated levels of Pb in the environment. Numerous studies have linked the PbB content of young children with the Pb content of soil or house dust (9,10,12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)25,26). These studies indicate that exposure to Pb via contaminated soil or house dust is responsible for a significant amount of the Pb burden in children.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have correlated PbB levels with airborne Pb or Pb in weathered paint (15,16,21,22,26). Several studies have indicated that the exposure to Pb occurred via contact with soil and not directly from air or paint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations